Isolation of a chrystalline compound from Uvaria scandens, C.C. Rob. (Anonaceae) - Guevara, Beatrice Q.
A pentacyclic triterpene was isolated from Uvaria scandens by chromatographic methods. The triterpene (C30 H50 O) m.p. 282-283(degrees) was identified as taraxerol from its infrared and mass spectra and by comparative thin-layer chromatography and mixed-melting point determination with an authentic sample. Its acetyl ester derivative was prepared and a comparison was made of their infrared spectra and thin-layer chromatographic pattern.
Available to the general public.
Thesis (Master of Science in Chemistry)--University of Santo Tomas, June 1972.
Keywords: Triterpenes; Uvaria scandens; Plants -- Chemical analysis; Phytochemistry